Socio-Demographic and Health Profile of Indoor Pediatric Patients Admitted in VS General Hospital, Ahmedabad - Kapil J Govani; Amul B Patel (Medsci Publications, 2016)
Introduction: Children under 15yr. of age comprise about 35.3% of India's population. The study was conducted to assess socio-demographic profile of pediatric patients and to assess the health status and probable etiology for hospitalization among them. Methodology: A cross sectional study was conducted among indoor pediatric patients under 15 yr age group admitted in V.S. general hospital, Ahmedabad during February to June 2015. Pretested Performa was used for study after informed consent of their parents. Results: Out of 193 children, majority (31.1%) were belongs to 0 to 2 yr age group. Major cause for hospitalization was gastrointestinal diseases (24.9%) followed by respiratory diseases (22.8%). 81(42%) children were malnourished. Gender wise significant difference was found among children for malnutrition status (P= 0.006). Majority children (upto 5yr) were partially immunized (56.5%). An average hand hygienic practice was noted of parents. Conclusion: Significant gender wise age distribution was noted. Almost half of admitted children (42%) were malnourished. Higher number of infectious diseases (gastrointestinal and respiratory) might be due to improper hygienic measures, average literacy and low socio-economic condition of family. Higher dropout rate was noted in immunization.